2022
DOI: 10.1128/jvi.01455-21
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Susceptibility of Ferrets to SARS-CoV-2 Infection

Abstract: Susceptibility to SARS-CoV-2 and the outcome of COVID-19 have been linked to underlying health conditions and the age of affected individuals. Here we assessed the effect of age on SARS-CoV-2 infection using a ferret model. For this, young (6-month-old) and aged (18-to-39-month-old) ferrets were inoculated intranasally with various doses of SARS-CoV-2. By using infectious virus shedding in respiratory secretions and seroconversion, we estimated that the infectious dose of SARS-CoV-2 in aged animals is ∼32 plaq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…The high amounts of infectious virus recovered from nasal turbinate and tonsils (viral titers ranged from 3.3 to 6.5 log10 TCID 50 .g -1 ) are consistent with intense viral RNA and N protein staining observed in situ and with the viral load and shedding patterns detected in respiratory secretions. This indicates that nasal turbinate and tonsil are likely the primary sites of viral replication during infection in WTD, which is similar to observations in other animal species and in humans [ 19 , 26 29 ]. Following infection and replication in these sites, the virus likely disseminates to draining lymph nodes, the lower respiratory (trachea and lung) tract and the CNS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The high amounts of infectious virus recovered from nasal turbinate and tonsils (viral titers ranged from 3.3 to 6.5 log10 TCID 50 .g -1 ) are consistent with intense viral RNA and N protein staining observed in situ and with the viral load and shedding patterns detected in respiratory secretions. This indicates that nasal turbinate and tonsil are likely the primary sites of viral replication during infection in WTD, which is similar to observations in other animal species and in humans [ 19 , 26 29 ]. Following infection and replication in these sites, the virus likely disseminates to draining lymph nodes, the lower respiratory (trachea and lung) tract and the CNS.…”
Section: Discussionsupporting
confidence: 86%
“…Our study extends the knowledge regarding SARS-CoV-2 infection dynamics in WTD, an animal species with the potential to serve as a reservoir for the virus in the field. We defined that SARS-CoV-2 has a short window of infectivity and transmissibility in WTD, which is similar to what has been described in humans and other animal species [ 19 , 21 , 27 , 29 , 36 38 ], and demonstrated that the virus presents a broad tissue tropism and multiple replication sites in this species. This information is critical to assess the relevance of natural SARS-CoV-2 infections in WTD populations and the potential risk of zoonotic spillback into humans.…”
Section: Discussionsupporting
confidence: 73%
“…Finally, studying older patients might determine whether the upregulation of ACE2 or the decrease in antibodies with senescence is significant ( 10 , 57 ). Moreover, the implications of ACE2 upregulation would lead to specific studies based on different symptoms in old and young patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first study described a significant expression of ACE2 in older males in both mouse models and human organs ( 10 ). The second study demonstrated the overexpression of ACE2 and TMPRSS2 in the upper respiratory tract of aged ferrets compared to young animals ( 57 ). Moreover, a recent study found that ACE2 levels increase during aging in mouse and human lungs due to telomere shortening or dysfunction ( 58 ).…”
Section: Relationship Between Abo Blood Group and Covid-19 Severity A...mentioning
confidence: 96%
See 1 more Smart Citation